Adjuvant Osimertinib vs. Placebo in Completely Resected Stage IA2–IA3 EGFR-Mutated NSCLC: ADAURA2 - Tsutani, Yasuhiro; Goldman, Jonathan W.; Dacic, Sanja; Yatabe, Yasushi; Majem, Margarita; Huang, Xiangning; Chen, Allen; van der Gronde, Toon; He, Jie (Clinical lung cancer, 2023)
Osimertinib is a third-generation, irreversible, oral epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor (TKI) that potently and selectively inhibits both EGFR-TKI sensitizing and EGFR T790M resistance mutations, with demonstrated efficacy in EGFR mutation-positive (EGFRm) non–small cell lung cancer (NSCLC), including central nervous system (CNS) metastases. Here we present the rationale and study design for ADAURA2 (NCT05120349), which will evaluate adjuvant osimertinib vs. placebo in patients with stage IA2–IA3 EGFRm NSCLC, following complete tumor resection. ADAURA2 is a phase III, global, randomized, double-blind, placebo-controlled study. Patients will be adults aged ≥18 years with resected primary nonsquamous NSCLC stage IA2 or IA3 and central confirmation of an EGFR exon 19 deletion or L858R mutation. Patients will be stratified by pathologic risk of disease recurrence (high vs. low), EGFR mutation type (exon 19 deletion vs. L858R) and race (Chinese Asian vs. non-Chinese Asian vs. non-Asian), and randomized 1:1 to receive osimertinib 80 mg once daily (QD) or placebo QD until disease recurrence, treatment discontinuation, or a maximum treatment duration of 3 years. The primary endpoint of this study is disease-free survival (DFS) in the high-risk stratum. Secondary endpoints include DFS in the overall population, overall survival, CNS DFS, and safety. Health-related quality of life and pharmacokinetics will also be evaluated. Study enrolment began in February 2022 and interim results of the primary endpoint are expected in August 2027.